OCCURRENT THOUGHT AND A PRIORI REASON IN CHIMPANZEES. - LURZ, ROBERT (Crítica)
Drawing on recent findings in cognitive neuroscience on aha-experiences in humans, I develop and defend the occurrent-thought hypothesis, which holds that chimpanzees evolved the ability for aha-experiences/occurrent thoughts to make their unconscious inferential reasoning abilities more effective. I argue that the occurrent-thought hypothesis provides a better explanation than the inference-only hypothesis for a range of facts about chimpanzees' inferential reasoning abilities. I recommend more direct empirical tests of the hypothesis and describe three experimental protocols. I end by drawing out the philosophical implications of the hypothesis for the evolution of a priori reason in humans and chimpanzees.